Adsorption equilibrium and kinetics of reactive black 5 and reactive red 239 in aqueous solution onto surfactant-modified zeolite - Karadag, Dogan; Turan, Mustafa; Akgul, Eda; Tok, Sema; Faki, Ayseguel (AMER CHEMICAL SOC, 2007)
The adsorption of Reactive Black 5 and Reactive Red 239 in aqueous solution on cetyltrimethylammonium bromide (CTAB)-zeolite was studied in a batch system. The natural zeolite and CTAB-modified zeolite were characterized by FIF-IR and SEM analysis. Experiments were performed at different conditions such as initial dye concentration, contact time, temperature, and pH. CTAB modification covered the zeolite surface with positive charges, and the adsorption capacity of zeolite increased. The adsorption capacity of Reactive Red 239 was found to be two times higher than Reactive Blue 5 due to the hydrophilicity of the dye molecules. The Langmuir and Freundlich adsorption models were applied to describe the equilibrium isotherms at different temperatures, and the Freundlich agrees very well with the experimental data. The pseudo-second-order model provided a very good fitting (R-2 > 0.992) for the two anionic dyes. The calculated maximum adsorption capacity (q(e,calcd)) increased with increasing initial dye concentration, but there is no linear relationship with pH and temperature. Thermodynamic parameters such as change in free energy (Delta G degrees), enthalpy (Delta H degrees), and entropy (Delta S degrees) were also determined.
Keywords: ACTIVATED CARBON; COLOR REMOVAL; AZO DYES; SORPTION; WATER; MODEL; Thermodynamics; Chemistry; Engineering